ANALISIS UNDANG-UNDANG HUKUM KELUARGA MESIR NOMOR 100 TAHUN 1985 PASAL 11 TENTANG POLIGAMI DAN RELEVANSINYA DENGAN MAQASHID SYARIAH - Zulkayandri; Zul Ikrami; Irsan (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2022)
This study examines and analyses the Egyptian Family Law Number 100 of 1985 Article 11 concerning polygamy and its relevance to maqashid sharia. This research is a library research, and the data analysis technique used in this research is content analysis and deductive analysis approach. This study concludes that, firstly, the substance of the Egyptian Family Law Number 100 of 1985 Article 11 concerning polygamy is: a. The husband must explain his marital status in the marriage certificate. b. The husband who will be polygamous must explain in a statement, the names of his wives and their places of residence. c. The notary must notify the first wife of her husband's marriage. d. A wife whose husband is polygamous can file for divorce if she experiences material or immaterial harm. e. If the judge is unable to reconcile between the husband and his first wife or his previous wives, the judge separates the two with the status of talak bain. f. The right of filing for divorce for the first wife or the previous wives is abolished if one year has elapsed since they ascertained of their husband's new marriage. g. The new wife can file for divorce if it turns out that her husband is hiding his old marriage. Secondly, this study concludes that the Egyptian Family Law Number 100 of 1985 Article 11 is relevant to maqashid sharia, the maqshad ashli (main goal) in it is hifzhun nasl, which is preserving the lineage and the continuity of offspring. As for the maqashid tab'iah (supporting goal) in the law is to create tranquillity in married life, the protection of the wives and children’s rights, and the protection of the husband’s rights